Causes of growth rate inhibition in lactose - Blyth, Kristy Michelle (Curtin University, 2013)
Lactose, a by-product of dairy processing, crystallizes slowly and unreliably. Purified lactose was obtained for baseline crystal growth behaviour. A new method to achieve this was developed. The impact of process-relevant impurities on crystal growth relative to the baseline was studied. Sugar phosphates were found to inhibit growth. Using inorganic salts it was found that ion pairs can have an impact on crystal habit. This may explain some of the discrepancies in the literature.